2019
DOI: 10.1097/pai.0000000000000678
|View full text |Cite
|
Sign up to set email alerts
|

Lepidic, Papillary Components and EGFR Mutations are Frequent in Patients With Lung Adenocarcinoma Who are Over 75 Years Old

Abstract: Treatment for lung adenocarcinoma frequently diverges from standard treatment in older patients. Clinical, pathologic, and molecular characteristics of lung cancer in patients over 75 years old have not been fully described. The aim of our work was to describe the rate of EGFR, KRAS, BRAF, and HER2 mutations, and ALK rearrangement and pathologic characteristics in patients with lung adenocarcinoma over 75, compared with patients below 75 years old. This is a retrospective study from 2 cohorts: a histopathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…Compared with other rare histologic subtypes of lung cancer, such as papillary adenocarcinoma (11) and carcinosarcoma (12), our results suggested that the incidence of LPA was much higher. Our results also indicated that LPA patients were more common in older age and females, which is consistent with previous studies (13,14). In addition, some clinicopathological features of LPA patients indicated a good prognosis, including smaller tumor size, fewer separate tumor nodules, less pleural invasion, and lower histological grade and stage.…”
Section: Discussionsupporting
confidence: 92%
“…Compared with other rare histologic subtypes of lung cancer, such as papillary adenocarcinoma (11) and carcinosarcoma (12), our results suggested that the incidence of LPA was much higher. Our results also indicated that LPA patients were more common in older age and females, which is consistent with previous studies (13,14). In addition, some clinicopathological features of LPA patients indicated a good prognosis, including smaller tumor size, fewer separate tumor nodules, less pleural invasion, and lower histological grade and stage.…”
Section: Discussionsupporting
confidence: 92%
“…The solid predominant subtype is the most frequently encountered subtype in our work, representing 42% of patients, which is higher than the percentage encountered for primary tumors [19]. Although two distinct unmatched cohorts cannot be directly compared, this might reflect the aggressiveness of tumors with solid subtypes.…”
Section: Discussionmentioning
confidence: 74%
“…These encouraging results highlight the feasibility and potential therapeutic impact of molecular testing in older patients. This attitude is supported by studies showing favorable outcomes of tyrosine kinase inhibitors in first- or second-line treatment in older or frail patients with EGFR mutation-positive non-small cell lung cancer [ 15 , 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 95%